Eulenburg's Aussenhandel - Graham, Frank D. (Quarterly Journal of Economics, 1929)
Journal Article Eulenburg's Aussenhandel Get access Frank D. Graham Frank D. Graham Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 44, Issue 1, November 1929, Pages 159–163, https://doi.org/10.2307/1885444 Published: 01 November 1929